Alignment and Alignment Transition of Bent Core Nematics - Hegde, Gurumurthy; Elamain, Omaima; Komitov, Lachezar (AIP Publishing LLC., 2013)
We report on the alignment of nematics consisting of bimesogen bent core molecules of chlorine substituent of benzene derivative and their binary mixture with rod like nematics. It was found that the alignment layer made from polyimide material, which is usually used for promoting vertical (homeotropic) alignment of rod like nematics, promotes instead a planar alignment of the bent core nematic and its nematic mixtures. At higher concentration of the rod like nematic component in these mixtures, a temperature driven transition from vertical to planar alignment was found near the transition to isotropic phase.